Fibonacci Numbers in Action - Mulatu, Lemma; Tierra Jones; Jonathan Lambright (IJRDO -JOURNAL OF MATHEMATICS, 2020)
An example of the power of math can be found in Fibonacci numbers.  The Fibonacci numbers are sequences of numbers of the form: 0,1,1,2,3,5,8,13,...  These numbers are famous for possessing wonderful and amazing applications. The sequence plays a central role in elementary number theory. In mathematical terms, it is defined by the following recurrence relation:                                               The first number of the sequence is 0, the second number is 1, and each subsequent number is equal to the sum of the previous two numbers of the sequence itself. That is, after two starting values, each number is the sum of the two preceding numbers. The  Fibonacci  numbers appear in an  amazingly variety of creations, both natural and people made. The numbers have very interesting properties, and keep popping up in many places in nature and art In this paper. The Fibonacci sequence also makes its appearance in many different ways within mathematics. In this paper we investigate some important applications of the Fibonacci numbers.